Substituted 2-[(2-Oxo-2H-[1,2,4]triazino [2,3-c]quinazolin-6-yl)thio]acetamides with Thiazole and Thiadiazole Fragments: Synthesis, Physicochemical Properties, Cytotoxicity, and Anticancer Activity - Kovalenko, Sergey I. (Österreichische Apotheker-Verlagsgesellschaft, 2012)
The series of novel N-R-2-[(3-R-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)thio]acetamides with thiazole and thiadiazole fragments in a molecule were obtained by alkylation of potassium salts 1.1–1.4 by N-hetaryl-2-chloroacetamides and by aminolysis of activated acids 2.1–2.4 with N,N’-carbonyldiimidazole (CDI). The structures of compounds were determined by IR, (1)H NMR, MS, and EI-MS analysis. The results of cytotoxicity evaluated by the bioluminescence inhibition of bacterium Photobacterium leiognathi, Sh1 showed that the compounds have considerable cytotoxicity. The synthesized compounds were tested for anticancer activity in NCI against 60 cell lines. Among the highly active compounds 3.1, 3.2, and 6.5, 2-[(3-methyl-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)thio]-N-(1,3-thiazol-2-yl)acetamide (3.1) was found to be the most active anticancer agent against the cell lines of colon cancer (GI(50) at 0.41–0.69 μM), melanoma (GI(50) 0.48–13.50 μM), and ovarian cancer (GI(50) 0.25–5.01 μM). The structure-activity relationship (SAR-analysis) was discussed.